Development of Islamic Human Resource Management in The Digital Era For MSMEs and Cooperatives in Indonesia - Ichsan, Reza Nurul; Syahbudi, Muhammad; Nst, Venny Fraya Hartin (LPPM, Universitas Islam Syarifuddin Lumajang, 2023)
Islamic human resource development through training and human resource management not only in terms of increasing intellectual abilities, but also emphasizing moral depth that comes from spiritual or religious origins. Therefore, the material in training or development must contain the values of Etqan, Ihsan, and al-Falah and also is aimed at to determine the role and also the impact of coaching, training and mentoring from Indonesian Ministry of Cooperatives and SMEsin improving the business performance of their assisted MSMEs through the Fast Track of Digitalization of 1000 Dignified MSMEs. The Implementation Method is chosen at this training. By taking 1000 assisted MSME actors who participated in the coaching, training and mentoring program provided by Indonesian Ministry of Cooperatives and SMEsfor 3 months. This training is carried out directly through the process of training and mentoring MSMEs and other supporting things obtained online and offline.